(untitled) (Research, Society and Development, 2021)
Cysts are pathological cavities covered by epithelial tissue. Periapical cysts are the most common cystic lesions of the jaws and originate from a granuloma, through a chronic inflammatory process, which stimulates the proliferation of epithelial remnants in the peri-apex region. They are asymptomatic and are considered radiographic findings. The treatment of periapical cysts varies according to the extent of the lesion. Objective: To describe a clinical case of removal of a periapical cyst combined with apicectomy, retrofilling and filling the cystic cavity with blood concentrate. Case report: Patient E.L.G, male, 43 years old, went to the dental clinic with the main complaint of “teeth breaking”. During anamnesis and clinical examination, a volumetric increase in soft consistency was noted at the bottom of the anterior buccal ridge of the maxilla, symptomatic to the touch, in the region of the right incisors. Panoramic radiography was requested and a radiolucent lesion of defined limits was observed; with a bone sclerosis margin, approximately one and a half centimeters in its largest diameter, unilocular, rounded, involving the root apex of tooth 12 and extending to the region of tooth 11. The anatomopathological examination confirmed the diagnosis of periapical cyst. Cystic curettage was performed followed by apicectomy and retrofilling with MTA. To promote bone repair, it was decided to fill the cystic cavity with biomaterial A-PRF +. Considerations: A-PRF + was presented as an alternative of relevant importance in the control of the inflammatory condition, assisting in the soft and hard tissue repair process.